Transition process to the civil service law for local governments case: District Municipality of Paucara - Moran Cusi, Saul (2022)
The modernization of public management in local governments consists, among other things, in the implementation of the results-based approach. In this way, entities must continue to promote and implement measures and actions to improve goods and services for citizens. Among its characteristics is the strengthening of decentralization. For this reason, the public management modernization process has five pillars, including the Civil Service, which tries to perfect public servants based on meritocracy and turn them into true public managers. For this, the public system of SERVIR was created and promoted. The main objective of this article is to present the case of the District Municipality of Paucara, in its attempt to transition to the Civil Service Law, through revisions of the current regulatory framework. In the conclusions, information is provided to the public servants who participate in the management of a municipality, it contributes to creating the capacity to carry out the processes and procedures for the transition to the Civil Service Law and the analysis of the limitations found, in this way try to find solutions for the proper management of human resources.